PENGARUH PELATIHAN SIT-UP BESAR SUDUT 450, 900, DAN 1200 TERHADAP KEKUATAN OTOT PERUT - Meiriawati, Made (Jurnal Ilmu Keolahragaan Undiksha, 2013)
This study was aimed to determine the effect of differences influences of sit-up training 450, 900 and 1200 of the abdominal muscle strength.  The study based on a quasi experimental research design with modifide the randomized pre-test post-tes control group design.  Samples were the students of class X SMA Dharma Praja Denpasar on academic year 2012/2013, as much as 24 people. Abdominal muscle strength will measured with the knee bent lying sitting in performed  for 30 seconds. Data were analyzed by ANAVA one way test at significance level 0,05 using SPSS 16,0, and then data will proceed with least significant difference test to obtain a comparison between groups. The result using LSD, group 450 to the control group (9,167), group of 900 to the control group (18.833), and group 1200 to control group (34,677). Mean difference of group 1200 to 450 group is at value 25,500. Mean difference of group 1200 to 900 group is at value 15,833. From the analysis, it was concludes that the sit-up training 450, 900 and 1200 have a significant impact and influences the differences to abdominal muscle strength  for the students of class X SMA Dharma Praja Denpasar on academic year 2012/2013,in which 1200 treatment group had the highest impact on improving abdominal muscle strength.